(untitled) (Indian Journal of Public Health Research & Development, 2023)
Introduction: Although WHO recommended continuing sexual and reproductive health services during COVID-19 pandemic, the services were either stopped completely or limited. Hence our study aims to determine the challenges in the accessibility to family planning services as well as the impact on contraception and safe abortion services during COVID-19 era. Methods: This is a cross-sectional descriptive study conducted in the department of Obstetrics & Gynaecology, SRM hospital, Chennai from September 2021 to November 2021. Random sampling method was used to enroll participants after considering the inclusion and exclusion criteria. Results: Almost half of the study population (49.24%) faced difficulty in following any form of contraceptive measure amid pandemic. Non-availability of contraceptive supply (14.72%) was the major hurdle during the pandemic. Among the respondents who had terminated the pregnancy, the majority had done by general medical practitioner (66.67%) while only thirty-three percent terminated under specialist care. While comparing the complications during pregnancy termination, general medical practitioner approach led to more complications than specialist care. Conclusion: Non-availability of contraceptive supplies, FP services amid COVID-19 pandemic has exerted detrimental impact on the women reproductive health. Continuing FP and safe abortion services are essential during pandemic to sustain the success of high-quality reproductive services.